From uncertain diseases to uncertain vaccines. Experts’ failure in the light of policy response to the COVID-19 pandemic—the case of Poland - Tadeusz Józef Rudek; Aleksandra Wagner; Paulina Polak; Maria Świątkiewicz-Mośny (Critical Public Health)
The COVID-19 pandemic has become a great challenge for societies. The increasing rate of infections and mortality forced state authorities to conduct and justify immediate decisions concerning all aspects of social life. The decisions were taken in light of high uncertainties and non-knowledge. Societies across the world were faced with the difficult dilemma of choosing between a new disease with its unknown consequences and a new vaccine that was perceived to be insufficiently tested to eliminate potential harmful effects of the disease. The urgency to accelerate vaccine development and testing led many to view the process as a large-scale experiment on society. All this leaves room for an in-depth study of the civic epistemologies behind the decision-making during the pandemic. We analysed the period from the announcement of the pandemic by WHO on 11 March 2020 to January 2022 to reflect on the production, evaluation, and use of knowledge (and non-knowledge) present in the decision-making of the Polish government and advisory bodies. The analysis is based on three data sources: interviews with members of the three relevant advisory bodies, press analysis (April 2019 to April 2021), and the official positions of the aforementioned councils and teams. We argue that different strategies for dealing with uncertainty determine the responses of different advisory bodies and their performativity in relation to policy-making.